Skip to main content

Poisson Law

b(n,ย p)โ†’dP(ฮป)ย ifย nโ‰ซ1ย &ย pโ‰ช1ย &ย ฮป=npb(n,~p) \xrightarrow{d} P(\lambda) ~ \text{if} ~ n \gg 1 ~ \& ~ p \ll 1 ~ \& ~ \lambda = np

Proofโ€‹

limโกnโ†’โˆžb(n,ย p)=limโกnโ†’โˆž(nx)px(1โˆ’p)nโˆ’x=limโกnโ†’โˆžn!(nโˆ’x)!ย x!px(1โˆ’p)nโˆ’x\lim_{n \to \infty} b(n, ~p) = \lim_{n \to \infty} {n \choose x} p^x (1-p) ^{n-x} = \lim_{n \to \infty} {n! \over {(n-x)! ~ x!}} p^x (1-p) ^{n-x} =limโกnโ†’โˆžn!x!(nโˆ’x)!ฮปxnx(1โˆ’ฮปn)nโˆ’x=ฮปxx!limโกnโ†’โˆžn!(nโˆ’x)!1nx(1โˆ’ฮปn)nโˆ’x= \lim_{n \to \infty} {n! \over {x! (n-x)!}} {\lambda^x \over n^x} (1-{\lambda \over n})^{n-x} = {\lambda^x \over x!} \lim_{n \to \infty} {n! \over {(n-x)!}} {1 \over n^x} (1- {\lambda \over n})^{n-x} =ฮปxx!limโกnโ†’โˆžnnnโˆ’1nnโˆ’2nโ‹ฏnโˆ’x+1n(1โˆ’ฮปn)n(1โˆ’ฮปn)โˆ’x= {\lambda^x \over x!} \lim_{n \to \infty} {n \over n} {{n-1} \over n} {{n-2} \over n} \cdots {{n-x+1} \over n} (1 - {\lambda \over n})^n (1 - {\lambda \over n})^{-x} =ฮปxx!limโกnโ†’โˆž1โ‹…limโกnโ†’โˆžnโˆ’1nโ‹ฏlimโกnโ†’โˆžnโˆ’x+1nlimโกnโ†’โˆž(1โˆ’ฮปn)nlimโกnโ†’โˆž(1โˆ’ฮปn)โˆ’x= {\lambda^x \over x!} \lim_{n \to \infty} 1 \cdot \lim_{n \to \infty} {{n-1} \over n} \cdots \lim_{n \to \infty} {{n-x+1} \over n} \lim_{n \to \infty} ({1- {\lambda \over n}})^n \lim_{n \to \infty} ({1- {\lambda \over n}})^{-x} =ฮปxx!limโกnโ†’โˆž(1+โˆ’ฮปn)n=ฮปxeโˆ’ฮปx!= {\lambda^x \over x!} \lim_{n \to \infty} (1+ {-\lambda \over n})^n = {{\lambda^x e^{-\lambda}} \over x!}